Risk Factors to Caries Disease in Primary Teeth of Special Needs Patients - Maria Alice SOARES; Cláudia Marina de Sousa VIEGAS; Lia Silva CASTILHO; Vera Lúcia Silva RESENDE (Association of Support to Oral Health Research (APESB), 2007)
Purpose: To investigate the influence of bottle feeding, age, parental educational level, chronic use medication, gender, oral hygiene performed by patient/caregiver, previous orientation of caregivers regarding oral hygiene and treatment by specialists of several health fields on the presence of cavited carious lesions and restorations in primary teeth of cerebral palsy patients.Method: 141 records of children with cerebral palsy enrolled in the project "Dental Care to Patients with Specials Needs" of the School of Dentistry/UFMG were examined. These children came from the Minas Gerais State Rehabilitation Association and from the João Moreira Salles School, both located at the city of Belo Horizonte, MG, Brazil. Chi-square tests and logistic regression were used for statistical analysis.Results: There was positive association between caries experience and age (p=0.000) and the use of nursing bottle (p=0.002). These patients are bottle fed during a long period of their lives. In spite of this, 67.4% of the participants of this project did not present carious lesions or restorations. The other variables did not show association with dental caries.Conclusion: Nursing bottle and age are important factors that predispose cerebral palsy patients to develop carious lesions.